Correlation analysis between plasma circulating tumour deoxyribonucleic acid variations and survival in patients with hepatocellular carcinoma - Liu, Songtao; Chen, Jingjing; Wei, Qiaoxin; Wang, Jinhuan; Xiong, Fang; Guo, Jia; Wang, Yang; Liu, Mei (Frontiers in Oncology, 2026)
ObjectiveThis study aimed to analyse the variation of circulating tumour DNA (ctDNA) in patients with hepatocellular carcinoma (HCC).MethodsNewly diagnosed patients with HCC admitted between March 2022 and October 2023 were prospectively enrolled. Plasma ctDNA testing was performed before treatment, and clinical information, treatment regimens and survival data were collected.ResultsA total of 166 patients with HCC were enrolled, including 127 men and 39 women, with a mean age of 58.1±10.0 years. Of these, 137 patients were infected with hepatitis B virus, and 129 had underlying cirrhosis. According to the Barcelona Clinic Liver Cancer (BCLC) staging system, 74, 20, 52 and 20 patients were classified as stages A, B, C and D, respectively. Tumour mutation burden (TMB) ranged from 0 to 35.48 mutations per Mb; it increased with higher BCLC stages but decreased in stage D. The top five mutated genes were TP53 (39.8%), CTNNB1 (15.7%), LRP1B (12.0%), ARID1A (10.8%) and FAT3 (9.0%). Patients with TP53 and LRP1B mutations exhibited shorter survival (p < 0.05). Among the 54 patients who received systemic therapy, only those with LRP1B mutations had significantly reduced overall survival (OS) (p = 0.048). Cox multivariate survival analysis revealed that TMB and Child–Pugh scores were closely associated with OS. Regardless of tumour stage, LRP1B mutation was significantly correlated with OS in patients undergoing systemic therapy.ConclusionCirculating tumour DNA testing demonstrated that TMB is closely associated with OS in patients with HCC. Patients with HCC with LRP1B mutations had significantly shorter survival when receiving systemic therapy. Circulating tumour DNA testing holds considerable value in predicting HCC prognosis and may serve as a biomarker for assessing patient outcomes.